Implementation of Worship and Religious Preservation Obligations in Inpatients at YARSI Hospital - Nidya Rhenatama Angelia; Rifqatussa'adah Rifqatussa'adah; Fathul Jannah (Junior Medical Journal, 2023)
According to WHO, healthy involves a state of complete well-being which includes four dimensions: physical, mental, social and spiritual. A person's level of spirituality can affect his quality of life. In relation to the healing process, spirituality can be explained by holistic concepts and services in nursing. YARSI Hospital itself has conducted an assessment of the spiritual aspect among other Islamic hospitals entitled